2014
DOI: 10.31269/triplec.v12i2.572
|View full text |Cite
|
Sign up to set email alerts
|

Constructing (Il)Legitimate Democracy: Populism and Power Concentration in Newspaper Discourse on Venezuela

Abstract: Abstract:Despite scholarly consensus about the importance of the media for democracy, scant attention has been paid to what democracy means to journalistic discourse and how discourses on democracy are interrelated with legitimacy. The aim of this paper is to explore how (il)legitimate democracy is constructed in newspaper discourse. By using critical discourse analysis (CDA), this paper examines foreign news items about Venezuela, a country that under the presidency of Hugo Chávez has challenged the dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Journalism constitutes an arena for hegemonic struggles to occur (Abalo 2014;Allan 1998), and the reporting of cannabis legalization is part of the struggle for (re)defining the meaning of cannabis. Journalism is set in a context of social change, something that can affect the choices of angles, sources and language in the creation of news on cannabis, which can affect the ascription of legitimacy to different perspectives on cannabis.…”
Section: Journalism and (De)legitimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Journalism constitutes an arena for hegemonic struggles to occur (Abalo 2014;Allan 1998), and the reporting of cannabis legalization is part of the struggle for (re)defining the meaning of cannabis. Journalism is set in a context of social change, something that can affect the choices of angles, sources and language in the creation of news on cannabis, which can affect the ascription of legitimacy to different perspectives on cannabis.…”
Section: Journalism and (De)legitimationmentioning
confidence: 99%
“…Journalism plays a key role in the process of cultural hegemonythe moral and intellectual leadership that leading social groups exercise (Gramsci 1971)by constructing reality in ways that affirm or challenge established values, norms and power relations in society (Abalo 2014;Allan 1998). This study seeks to understand the relationship between journalism and hegemony in times when hegemonic values are being severely challenged by studying the journalistic construction of the ongoing international renegotiation of psychoactive substances deriving from the cannabis plant (hereafter cannabis) as a case.…”
Section: Introductionmentioning
confidence: 99%
“…Lazarsfeld and Merton (1974) suggested that one of the functions of mass media is to grant status to public issues and actors. That is, media help to legitimize and delegitimize certain structures and practices (Abalo, 2014). Legitimacy can be defined as the construction of something as "legally and morally acceptable" (Chouliaraki, 2005, p. 3).…”
Section: Concludesmentioning
confidence: 99%
“…Chávez's media policy has been characterized by attempts to combat oppositional media sources by exerting greater control over airwaves (Waisbord 2011) while increasing the supply of community media (Fernandes 2011). Furthermore, the opposition appears to be in an advantageous position compared to the government in foreign reporting representations of Venezuela, evidenced by constructions of the opposition as bringing national unity while the government is presented as authoritarian and polarizing (Abalo 2012(Abalo , 2014Salter and Weltman 2011).…”
Section: Understanding the Venezuelan Casementioning
confidence: 99%